Art psychotherapy meets creative AI: an integrative review positioning the role of creative AI in art therapy process - Zubala, Ania; Pease, Alison; Lyszkiewicz, Kacper; Hackett, Simon (Frontiers in Psychology, 2025)
BackgroundThe rise of artificial intelligence (AI) is promising novel contributions to treatment and prevention of mental ill health. While research on the use of conversational and embodied AI in psychotherapy practice is developing rapidly, it leaves gaps in understanding of the impact that creative AI might have on art psychotherapy practice specifically. A constructive dialogue between the disciplines of creative AI and art psychotherapy is needed, to establish potential relevance of AI-bases technologies to therapeutic practice involving artmaking and creative self-expression.MethodsThis integrative review set out to explore whether and how creative AI could enhance the practice of art psychotherapy and other psychological interventions utilizing visual communication and/or artmaking. A transdisciplinary search strategy was developed to capture the latest research across diverse methodologies and stages of development, including reviews, opinion papers, prototype development and empirical research studies.FindingsOf over 550 records screened, 10 papers were included in this review. Their key characteristics are mapped out on a matrix of stakeholder groups involved, elements of interventions belonging to art therapy domain, and the types of AI-based technologies involved. Themes of key significance for AT practice are discussed, including cultural adaptability, inclusivity and accessibility, impact on creativity and self-expression, and unpredictability and imperfection. A positioning diagram is proposed to describe the role of AI in AT. AI’s role in the therapy process oscillates on a spectrum from being a partner in the co-creative process to taking the role of a curator of personalized visuals with therapeutic intent. Another dimension indicates the level of autonomy – from a supportive tool to an autonomous agent. Examples for each of these situations are identified in the reviewed literature.ConclusionWhile creative AI brings opportunities for new modes of self-expression and extended reach of art therapy, over-reliance on it presents risks to the therapy process, including of loss of agency for clients and therapists. Implications of AI-based technology on therapeutic relationship in psychotherapy demand further investigation, as do its cultural and psychological impacts, before the relevance of creative AI to art therapy practice can be confirmed.